Conclusions and Future Directions - Krishnasamy, Ganesh; Kulkarni, Anand Jayant; Abraham, Ajith (Cohort Intelligence: A Socio-inspired Optimization Method, 2016)
This book provided detailed state-of-the-art developments on the emerging socio-inspired metaheuristic technique of Cohort Intelligence (CI). The motivation of the methodology is also discussed in detail. The methodology was successfully tested and validated by solving several unconstrained problems with different modalities and dimensions. The solution quality was quite promising and encouraging in terms of objective function, robustness, avoidance of local minima, computational time and function evaluations. The effect of each individual parameter such as sampling interval reduction factor, number of candidates and number of variations on the computational performance was also tested.